Systematic Review: The Epidemiology, Natural History, and Burden of Alagille Syndrome - Kamath, Binita M. (J Pediatr Gastroenterol Nutr, 2018)
BACKGROUND AND AIM: Alagille syndrome (ALGS) is an inherited multisystem disorder typically manifesting as cholestasis, and potentially leading to end-stage liver disease and death. The aim of the study was to perform the first systematic review of the epidemiology, natural history, and burden of ALGS with a focus on the liver component. METHODS: Electronic databases and proceedings from key congresses were searched in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 guidelines. This analysis included publications reporting epidemiology, natural history, economic burden or health-related quality of life (HRQoL) outcomes in patients with ALGS. RESULTS: Of 525 screened publications, 20 met the inclusion criteria. Liver-related features included cholestasis (87%–100% of patients), jaundice (66%–85%), and cirrhosis (44%–95%). Between 15% and 47% of patients underwent liver transplantation and 4% to 14% received partial biliary diversion. Pruritus affected the majority of patients (59%–88%, of whom up to 45% had severe pruritus) and manifested during the first 10 years of life. Children with ALGS had significantly impaired HRQoL compared with healthy controls and those with other diseases. Itching was the symptom that most affected children with ALGS. No study assessed the economic burden of ALGS. CONCLUSIONS: Our findings consolidate information on the clinical course of ALGS, and highlight gaps in knowledge, most notably the absence of any research on the economic consequences of the disease. Further research is needed to establish the incidence of genetically confirmed ALGS. Disease-specific tools are also needed to improve the measurement of symptoms, such as itching, and better understand the impact of ALGS on HRQoL.